SWOT matrix analysis of the enhancing the effectiveness of education in the context of digitalization. Issue 1 (August 2021) - Mushkarova, O; Mikheeva, M; Nefedova, I; Chepic, F; Vasiliev, S
Abstract: The article discusses the opportunities and threats of distance education in order to form the full scale competencies of the students. Based on the results of the study, the reasoning of the application of the most effective rational techniques, teaching methods based on digital technologies in the offline learning mode is given.